211k views
4 votes
Solve the equation.

−4(n−6)=12

2 Answers

4 votes

Answer:

Explanation:

-4(n-6)=12

=n-6=12/-4

( this step is because -4 is multiplied to n-6, si we move it to the right side so the signs always change so multiplication becomes division.)

= n-6=-3

=n= -3+6

(When we shift places signs change so -6 becomes +6)

= n= 3

User Damarys
by
4.8k points
1 vote

Answer:

n = 3

Explanation:

Given

- 4(n - 6) = 12 ← divide both sides by - 4

n - 6 = - 3 ← add 6 to both sides

n = 3

User Pbanka
by
5.8k points